с − 2p
2
c; 11) x
3 − xy
2 + 3y
2 − 3x
2
;
4) x
3 + 2x
2 + x; 12) x
2 − 10x + 29;
5) −a
2 + 8ab − 16b
2
; 13) (a
3 + 8b
3
) + (a
2 − 2ab + 4b
2
);
6) 75a
2 − 3b
2
; 14) a
2 + 2a + 1 − b
2
;
7) x
4 − y
4
; 15) c
2 − 6c + 9 − d
2
;
8) 6x
2 + 12xy + 6y
2
; 16) x
3 + x
2 − x − 1.
1) a)y=3 б)x=3 в) (3;+∞) возрастает (-∞;3) убывает
2)а)у=-0,5 б) у=0,25 в) у=3
3) у(4)>y(3) y(-3)>y(-2) y(2)<y(-5)
Объяснение:
1) находим по графику абсцисса -это х ордината это -у
2)подставляем вместо х значение и считаем
3) a)у(4)==16 б)у(-3)==9 в) у(2)==4
у(3)==9 у(-2)==4 у(-5)==25
у(4)>y(3) y(-3)>y(-2) y(2)<y(-5)